Professional care of the person with a stoma in Poland - Cierzniakowska, Katarzyna; Szewczyk, Maria T.; Banaszkiewicz, Zbigniew; Jawień, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2010)
In Poland, in practice a very important role falls to the nursing model of care for patients with a stoma, which governs the application of various procedures and instructions, eg in the field of education, the designation of the future stoma, fitting the patient\'s ostomy and other appliances. Involvement in the medical-therapeutic care of the whole team, people with a stoma, and also their relatives with whom they remain in the family and social relationships increase the likelihood of achieving a high level of quality of life with a stoma. The main aim of this article is to present the facts of nursing care for a person with stoma in Poland, which consists, inter alia, alignment of self-care deficits, reducing postoperative complications, educating both patients with a stoma and his family and other activities affecting the quality of life.